Успадкування морфологічних ознак залозистих волосків в потомстві - Горшкова, Л.М.; Богданова, А.С.; Вировець, В.Г. (Фактори експериментальної еволюції організмів, 2013)
Aims. The article deals with the research of inheriting the morphological features of gland hairs by the posterity. The connection between the existence of the gland hairs and the concentration of cannabinoids in the hemp plants was investigated. The selective work was aimed at lowering the cannabinoids content in the hemp plants by means of selecting the plants with less gland hairs as they are mainly the bearers of the substance. Methods. During the investigation the stereoscopic microscope was the main device and the method of the thin layer chromatography was used. The cannabinoids quantity was defined by the gas and liquid chromatograph of the type Hewlett Packard 3380 A. The inner standard of the experiment was methyl ether of the stearin acid C19H38O2. Results. The second generation hybrids demonstrated splitting by the phenotype. The hybridological analysis proved dominating the gland hairs over their absence. Conclusions. Besides the interaction of two dominant genes was shown as the new morphological feature - the gland form which was the proof of the genes complementary result.

Key words: lowering the cannabinoids content, gland hairs, inheriting, morphological features, thin layer chromatography method.